Students' Perception of Using Google Classroom in The Paragraph Writing Class at English Education Department - Ridwan, Nur Marwinda; Muhsin, Muh. Arief; Mahmudah, Dzur Rif’ah (FKIP Unismuh Makassar, 2022)
This study aims to determine the perception of each student in using Google Classroom in the second semester paragraph writing course at the Department of English Education, Unismuh Makassar. In this study used quantitative research method. The data was collected through distributing questionnaires to each student. The sampling technique used by the researchers in this study was purposive sampling. The sample in this study were 27 students consisting of 14 students from class BG2A and 13 students from class BG2B class 2021 majoring in English Education. The results of this study was showed the variable that achieves the highest index was the